Assessment of the children hurting phenomenon in the context of ethics - Waksmańska, Wioletta; Łukasik, Renata; Grzywna, Teresa (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. Bullying a family poses a threat to the health and life of all of the family members. Worrying is the fact that the forms of violence used by the parents against the child are refined and hidden, which makes it difficult to the persons from outside of the family to perceive the irregularities. Aim. The objective of the paper has been to examine the frequency of occurring of the children hurting phenomenon in the opinion of pediatric nurses and the most frequent symptoms confirming children hurting observed by them. Assessment of the attempt to determine the ethical conduct of the polled professional group with regard to the ethical code, in reference to violence in the family. Material and methods. The analysis was made based on anonymous opinion polling performed among 149 nurses in the Silesian pediatric hospital. The nurses have been asked how often in their work they have been meeting the children hurting problem and what symptoms confirming children hurting they have met. A question was asked whether the respondents reacted to the problem and what they reactions have been. The second part of the questionnaire included open questions on ethical conduct and the importance of „ethics” for a nurse. Descriptive statistics has been applied in the analysis of the received results. Results and conclusions. Based on the questionnaires, it has been determined that 77.8% of the polled nurses have met children that have been hurt. The most often observed symptoms of hurting children were bruises, neglect and intimidation. Among the nurses who met children that have been hurt, 42% have not reacted to the problem at all, while 28.4% of them thought they act ethically.